Asymptotic distinguishing of reconstruction processes - Lynkov, Yu. N.; Munir el Shakf, (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Limit theorems for the logarithm of the likelihood ratio are proven. With their help the rate of decrease in the probability of errors of the second kind in the Neumann–Pierson criterion is established.